Reasons and Hindrances of the Community Leaders in Releasing Stocked Persons with Mental Problems in Southern East Sulawesi - Abdul Patawari; Titin Andri Wihastuti; Nurul Muslihah; Asti Melani Astari; Yulian Wiji Utami (Jurnal Kedokteran Brawijaya, 2021)
Undertaking stock punishment is an action to immobilized individuals that suffer mental health disorders. It is mostly done by placing woods on individuals' ankles. They are designed to restrict the patients' movements and made from wooden bars. The patients are chained or locked in a special room. A community leader, as the leader of certain people, has important roles in undertaking the stocks. It is done by considering various reasons based on the constructed understanding and emerging assumptions in the middle of society. This research aims to explore the reasons and hindrances of the community leader in releasing the stocks undertaken on individuals with mental health disorders. The applied research method is qualitative research with an interpretative phenomenology. 7 participants were selected by using purposive sampling. Then, an analysis was carried out by the Interpretative Phenomenological Analysis (IPA). The findings dealing with the reasons for the community leader to undertake the stocks consisted of two themes. They dealt with the administered medication to recover individuals with mental health disorders and to protect them, their families, and society. Meanwhile, the hindrances of the community leader in discharging or releasing the punishment dealt with the difficulty to get psychiatric service. The conclusions are the stocks reasons deal with a lack of the community leader's understanding to care for the individuals with mental health disorders and the necessity of active participation of medical officers. Thus, the people could obtain maximum psychiatric service